Wisdom for changing times insights on faith, finances & freedom for the days ahead - Robertson, Pat.; Robertson, Gordon, 1958- (Virginia Beach, Va. : Christian Broadcasting Network, 2008)
Pat Robertson interacts with a live studio audience addressing vital issues of faith, finances and freedom for the days ahead. This valuable teaching will build your faith and give you scriptural keys to tapping into God's rich store of wisdom and knowledge for these changing times.
Pat Robertson: Part 1, Widsom for our economy -- Part 2, Wisdom for our nation and the world -- Part 3, Wisdom of God's protection. Gordon Robertson: Part 1, New resources for you -- Part 2, New 3-D superbook -- Part 3, Proclaiming the Gospel around the world -- Part 4, Lives you've changed through your partnership.
Pat Robertson, Gordon Robertson.
DVD.
Title from cover.
Special bonus: Gordon Robertson brings insights into the key role you are playing in global evangelism. You'll also discover important resources to help strengthen your relationship with God and share His love with a world in need.
Keywords: Christian life; Finance, Personal -- Religious aspects; DVD-Video discs